Quantification of von Willebrand factor and ADAMTS-13 after traumatic injury: a pilot study. Issue 1 (5th April 2021) - MacArthur, Taleen A; Goswami, Julie; Moon Tasson, Laurie; Tischer, Alexander; Bailey, Kent R; Spears, Grant M; Dong, Jing-Fei; Auton, Matthew; Kozar, Rosemary; Park, Myung S
Abstract : Background: Von Willebrand factor (VWF) is an acute phase reactant synthesized in the megakaryocytes and endothelial cells. VWF forms ultra-large multimers (ULVWF) which are cleaved by the metalloprotease ADAMTS-13, preventing spontaneous VWF–platelet interaction. After trauma, ULVWF is released into circulation as part of the acute phase reaction. We hypothesized that trauma patients would have increased levels of VWF and decreased levels of ADAMTS-13 and that these patients would have accelerated thrombin generation. Methods: We assessed plasma concentrations of VWF antigen and ADAMTS-13 antigen, the Rapid Enzyme Assays for Autoimmune Diseases (REAADS) activity of VWF, which measure exposure of the platelet-binding A1 domain, and thrombin generation kinetics in 50 samples from 30 trauma patients and an additional 21 samples from volunteers. Samples were analyzed at 0 to 2 hours and at 6 hours from the time of injury. Data are presented as median (IQR) and Kruskal-Wallis test was performed between trauma patients and volunteers at both time points. Results: REAADS activity was greater in trauma patients than volunteers both at 0 to 2 hours (190.0 (132.0–264.0) vs. 92.0 (71.0–114.0), p<0.002) and at 6 hours (167.5 (108.0–312.5.0) vs. 92.0 (71.0–114.0), p<0.001). ADAMTS-13 antigen levels were also decreased in trauma patients both at 0 to 2 hours (0.84 (0.51–0.94) vs. 1.00 (0.89–1.09), p=0.010) and at 6 hours (0.653 (0.531–0.821) vs. 1.00 (0.89–1.09), p<0.001). Trauma patients had accelerated thrombin generation kinetics, with greater peak height and shorter time to peak than healthy volunteers at both time points. Discussion: Trauma patients have increased exposure of the VWF A1 domain and decreased levels of ADAMTS-13 compared with healthy volunteers. This suggests that the VWF burst after trauma may exceed the proteolytic capacity of ADAMTS-13, allowing circulating ULVWF multimers to bind platelets, potentially contributing to trauma-induced coagulopathy. Level of evidence: Prospective case cohort study.